A simple solvent-based sintering method for fabricating hierarchal porous UHMW polyethylene structures for high solar reflectivity and sub-ambient cooling - Dunna Sujith; Chandaswi Borra; Gaurav Kumar; Sarthak S. Singh; Olivier Lame; Kesavan Ravi (Next Materials)
This study presents a novel o-xylene solvent-based sintering approach for fabricating hierarchal porous ultra-high molecular weight polyethylene structures, aimed at achieving high solar reflectance (Rsolar̅) and sub-ambient cooling. The bottom up, scalable method enables the fabrication of surfaces with high Rsolar̅ while maintaining the possibility of easy installation on rooftop surfaces for space cooling applications in buildings. Fabricated ultra-high molecular weight polyethylene (UHMWPE) surfaces exhibit an Rsolar̅ of 93 %, thermal conductivity of 0.1417 W/mK and an average sub-ambient cooling performance of ∼4.7 °C when exposed to direct sunlight. The high Rsolar̅ of the fabricated samples are attributed to a hierarchal micro-nano porous structure due to the solvent-assisted sintering process. The high sub-ambient cooling performance may be attributed to a combinatory effect of solar reflectance, thermal conductivity and thermal emissivity of UHMWPE film.